نقص الكلس الباكر عند الوليد دراسة لمعرفة شيوعه، أسبابه، أعراضه، سبل كشفه باكراً - يني, هلا; أصلان, سمير; قرا, نائلة (Latakia University Journal -Medical Sciences Series, 2019)
يتعرض الولدان الأصحاء إلى هبوط فيزيولوجي في مستويات الكلس المصلية بعمر 24 _ 48 ساعة وقد يبلغ هذا الهبوط مستويات نقص كلس الدم عند الولدان ذوي الخطورة العالية . الأهداف: تحديد نسبة شيوع نقص الكلس الباكر ودراسة الأسباب والتظاهرات السريرية مع تحديد طرق الكشف السريرية والمخبرية. طرائق الدراسة: تمت الدراسة في الفترة بين 1 ⁄ نيسان ⁄ 2007 و 31 ⁄ آذار ⁄ 2008 على 44 وليداً شخص لديهم نقص كلس دم باكر عن طريق معايرة كلس الدم الكلي في الأيام الثلاثة الأولى من العمر لجميع الولدان المقبولين في شعبة الحاضنات بمشفى الأسد الجامعي باللاذقية. النتائج: بلغت نسبة نقص الكلس 11 % وكان صامتاً سريرياً بنسبة 54.54%, لكن تظاهراته السريرية كانت متنوعة ومستقلة عن درجة نقص الكلس, وعن عوامل الخطورة, كما تعددت العوامل المسؤولة كالخداجة, الاختناق حول الولادة والسكري الحملي بينما لم يبرز نقص وزن الولادة كعامل خطورة مستقل . الخلاصة: يجب استقصاء نقص كلس الدم عند الولدان ذوي الخطورة العالية وهم الخدج, ولدان الأمهات السكريات, والولدان المتعرضين لاختناق حول الولادة. Healthy term neonates undergo a physiological nadir in serum calcium levels by 24-48 hours of age. This nadir may drop to hypocalcaemic levels in high-risk neonates. The main objective of this research is to study the prevalence of early neonatal hypocalcaemia, its causes, clinical manifestations, and methods of clinical and laboratory detection. This study was conducted during the period of April 1, 2007 and March 31, 2008. 44 neonates were diagnosed as having early hypocalcaemia by assaying total calcium during the first 3 days of birth for all admitted neonates to the Incubator Department of Al-Assad University Hospital, Lattakia, Syria. Prevalence of early hypocalcaemia reached 11%; it was asymptomatic in 54.54%; clinical manifestations were variable, independent of the degree of hypocalcaemia and risk factors; causes were numerous, such as prematurity, maternal diabetes, and prenatal asphyxia. Low birth weight was not an independent risk factor. To conclude, screening is recommended in risk neonates: preterm, neonate of a diabetic mother, and prenatal asphyxia.